Células-tronco em odontologia: perspectivas de aplicação e regeneração dentária – uma revisão de literatura. - Simon, Elisangela Fatima (2022)
Stem cells are undifferentiated cells with the ability to renew and differentiate into different cell types, thus originating the various groups of tissues in the human body. Stem cells can be categorized as either embryonic or adult stem cells. The study carried out refers to a literature review about stem cells in Dentistry, focusing on the application and dental regeneration. An update was sought regarding stem cell therapies and their potential, whether adult or embryonic, analyzing their pros and cons in their use. Data were collected through a search for scientific articles related to the subject, using the descriptors stem cells, dentistry, cell therapy and dental pulp, based on articles published between 2007 and 2022 on electronic platforms such as Bireme, Periodicos capes, Pubmed and Portal Cielo. The results show that despite the large studies carried out, the use of stem cells in dentistry has not become routine in daily therapeutic protocols, in the magnitude of its indications. Embryonic stem cells still have great limitations when compared to adult stem cells, which, in turn, have shown to be very promising. Studies with stem cells demonstrate the importance and the possibility of using these cells in the treatment of changes in dental structures, having the advantage of their ability to proliferate and differentiate into numerous cell types, making studies in this lineage progress (Silva Rosales et al. al., 2015; Bavaresco et al., 2020).